Roles of microRNAs in abdominal aortic aneurysm pathogenesis and the possibility of their use as biomarkers - Borek, Adam; Drzymała, Franciszek; Botor, Malwina; Auguściak-Duma, Aleksandra; Sieroń, Aleksander (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2019)
Abdominal aortic aneurysm (AAA) is a dangerous condition involving pathological dilation of the aortic wall. Due to the asymptomatic course of this disease and the dangerous consequences of its rupture, it is important to identify its specific bio-markers expressed as early as possible. Different expression profiles of microRNAs (miRNAs) were detected in patients diagnosed with AAA. MicroRNAs are small non-coding RNA molecules that regulate the expression of other genes at the translation stage. miRNAs affecting translation can lead to abnormal remodeling of extracellular matrix, inhibition of the cell cycle, cell aging or intensified inflammation. This review summarizes current knowledge about the role of microRNAs in the context of formation and development of abdominal aorta aneurysm and the possibility of using some miRNAs as bio-markers, and also provides basic information about miRNAs and aneurysms.